Anatomical morphology of the aortic valve in Chinese aortic stenosis patients and clinical results after downsize strategy of transcatheter aortic valve replacement. Issue 24 (20th December 2022) - Niu, Guannan; Ali, Walid Ben; Wang, Moyang; Jilaihawi, Hasan; Zhang, Haitong; Zhang, Qian; Ye, Yunqing; Liu, Xinmin; Yao, Jing; Zhao, Qinghao; Wang, Yubin; Zhou, Zheng; et al.
Abstract: Background: The study aimed to describe the aortic valve morphology in Chinese patients underwent transcatheter aortic valve replacement (TAVR) for symptomatic severe aortic stenosis (AS), and the impact of sizing strategies and related procedural outcomes. Methods: Patients with severe AS who underwent TAVR were consecutively enrolled from 2012 to 2019. The anatomy and morphology of the aortic root were assessed. "Downsize" strategy was preformed when patients had complex morphology. The clinical outcomes of patients who performed downsize strategy were compared with those received annular sizing strategy. The primary outcome was device success rate, and secondary outcomes included Valve Academic Research Consortium-3 clinical outcomes variables based on 1-year follow-up. Results: A total of 293 patients were enrolled. Among them, 95 patients (32.4%) had bicuspid aortic valve. The calcium volume (Hounsfield Unit-850) of aortic root was 449.90 (243.15–782.15) mm 3 . Calcium is distributed mostly on the leaflet level. Downsize strategy was performed in 204 patients (69.6%). Compared with the patients who performed annular sizing strategy, those received downsize strategy achieved a similar device success rate (82.0% [73] vs . 83.3% [170], P  = 0.79). Aortic valve gradients (downsize strategy group vs . annular sizing group, 11.28 mmHg vs. 11.88 mmHg, P  = 0.64) and percentages of patients with moderate or severe paravalvular regurgitation 2.0% (4/204) vs . 4.5% (4/89), P  = 0.21) were similar in the two groups at 30 days after TAVR. These echocardiographic results were sustainable for one year. Conclusions: Chinese TAVR patients have more prevalent bicuspid morphology and large calcium volume of aortic root. Calcium is distributed mostly on the leaflet level. Compare with annular sizing strategy, downsize strategy provided a non-inferior device success rate and transcatheter heart valve hemodynamic performance in self-expanding TAVR procedure.